Experimental performance investigation of high reflective and diffuse reflective concentrating photovoltaic/ thermal (CPVT) systems using non-imaging concentrators from energy, exergy, and economic viewpoint - Ustaoğlu, Abid; Buyukpatpat, Hakan; Kaya, Hüseyin; Kurşuncu, Bilal; Karaagac, Mehmet Onur; Okajima, Junnosuke; Kaya, Hüseyin; Büyükpatpat, Hakan; Kurşuncu, Bilal; Ustaoğlu, Abid (Pergamon-Elsevier Science Ltd, 2025)
A diffuse reflective (DR) surface in a concentrating photovoltaic thermal system (CPVT) system can provide uniform solar energy dispersion, minimizing hot spots, uneven lighting, and efficiency loss compared to costlier, highly reflective (HR) surfaces. This study uniquely compares the performance of HR-CPVT and DR-CPVT systems, highlighting the significant thermal and electrical efficiency of HR-CPVT while demonstrating the cost-effectiveness of DR-CPVT. The direct comparison of these systems under varying conditions provides novel insights into the trade-offs between high performance and economic feasibility. The performances of CPVTs were examined under various seasonal and weather conditions. The advantage of HR-CPVT was less pronounced in autumn due to seasonal effects. In the summer season, the cooling effect of water becomes more prominent, and the HR-CPVT outperformed the DR-CPVT by 6.1 to 8.5 %, depending on the mass flow rate in terms of overall efficiency. This advancement majorly arises from thermal efficiency. HR-CPVT achieved about a 5.6-7.9 % larger thermal efficiency. However, the electrical efficiency difference was minimal (similar to 0.5 %) and diminished to 0.1 % in the afternoon due to practical PV power generation limits. Despite its high reflectivity, HR-CPVT showed only marginal exergetic benefits over DR-CPVT. The simple payback period was calculated to be 3.65 years for HRCPVT, while it was only 3.19 years for DR-CPVT due to its lower installment cost. RSM analysis accurately predicts the experimental results.
Keywords: Concentrating Photovoltaic Thermal; Electric And Thermal Efficiency; Exergy; Response Surface Method; Net Present Value; Internal Rate Of Return